2001
DOI: 10.1007/s004640000356
|View full text |Cite
|
Sign up to set email alerts
|

Does a laparoscopic approach to total abdominal colectomy and proctocolectomy offer advantages?

Abstract: The results indicate that LTAC can be performed safely with a statistically significant reduction in wound and long-term postoperative complications, as compared with its open counterpart. Operating time is increased, but there is a marked reduction in length of hospital stay. Preliminary results demonstrate that LTPC also is technically feasible and safe, with equal morbidity, mortality, and hospital stay, as compared with open procedures. Studies with larger numbers of patients and a randomized controlled tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
86
4
6

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 25 publications
10
86
4
6
Order By: Relevance
“…Our data shows that this operation is feasible and safe with no mortality and acceptable morbidity, as reported in previous studies [3][4][5][6][7][8][9][10][11] (Table 5). The early postoperative results highlight problems with bowel function after total colectomy with a mean of 4.4 d until the first bowel movement.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Our data shows that this operation is feasible and safe with no mortality and acceptable morbidity, as reported in previous studies [3][4][5][6][7][8][9][10][11] (Table 5). The early postoperative results highlight problems with bowel function after total colectomy with a mean of 4.4 d until the first bowel movement.…”
Section: Discussionsupporting
confidence: 69%
“…For selected patients presenting with mild disease in the rectum, no dysplasia and with normal rectal compliance, a subtotal colectomy with ileo-distal sigmoid anastomosis may be an alternative and was performed in this study. Few published reports exist and mainly report techniques performed for a single indication or include small numbers of patients [3][4][5][6][7][8][9][10] . The aim of this study was to report the outcomes of laparoscopic total colectomy based on indication, comparing IBD with other indications.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Additional benefits of the minimally invasive approach appear to be a reduced incidence of early infectious wound complications and late incisional hernia formations in addition to the obviously improved cosmesis. [24][25][26][27] The association between high volume for surgeons and hospitals and better surgical outcomes is well documented for many surgical procedures. [28][29][30][31] The literature [32][33][34][35][36][37][38][39][40][41] suggests that this also applies to colorectal surgery for both the open and laparoscopic techniques.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,14,[18][19][20][21][22][23][24][25][26][27] Our group recently demonstrated significant advantages of laparoscopic colectomy over open colectomy with respect to the length of the hospital stay, rate of routine hospital discharge, and postoperative inhospital morbidity by performing a study of more than 18 000 patients with diverticular disease. 13 The acceptance of laparoscopic surgery in the field of colonic cancer has been hampered by the lack of prospective randomized trials with adequate follow-up periods providing equal oncological clearance and long-term course.…”
Section: Commentmentioning
confidence: 99%
“…However, with advances in technology and experience of laparoscopic surgery, more favourable results have been stated. Several studies have reported the feasibility and safety of laparoscopic assisted total colectomy for ulcerative colitis in the elective setting, and shown the advantages of laparoscopic assisted total colectomy such as reduced postoperative pain, earlier return of intestinal function, decreased length of hospital stay, and improved cosmesis (Marcello et al, 2000;Hashimoto et al, 2001;Seshadri et al, 2001;Gill et al, 2004;Kienle et al, 2005;Larson et al, 2005). On the basis of these results, several studies have evaluated the feasibility and safety of minimally invasive surgery for selected patients with severe ulcerative colitis (Dunker et al, 2000;Bell & Seymour, 2002;Marceau et al, 2007;Fowkes et al, 2008;Watanabe et al, 2009;Holubar et al, 2009;Chung et al, 2009;Maggiori et al, 2010;Telem et al, 2010).…”
Section: Resultsmentioning
confidence: 99%